Internal biogas reforming in solid oxide and proton conducting fuel cells: progress, challenges and perspectives - Stephanie E Wolf; Jan Uecker; Niklas Eyckeler; Leon Schley; L G J (Bert) de Haart; Vaibhav Vibhu; Rüdiger-A Eichel (JPhys Energy)
The internal reforming of biogas, a mixture containing carbon dioxide (CO _2 ) and methane (CH _4 ), in solid oxide and solid proton conducting fuel cells (SOFCs, SPCFCs) is a sustainable and efficient method to produce syngas (H _2 + CO) in combination with highly efficient electrical power generation. Reforming processes convert biogas into syngas by steam reforming, dry reforming, or partial oxidation, which then undergoes electrochemical reactions in the SOFCs/SPCFCs to produce electricity and heat. The dry methane reforming process of the anthropogenic greenhouse gases CH _4 and CO _2 into biogas can result in co-generation of electrical power and syngas mixtures of CO:H _2 relevant for large-scale industrial processes like the Fischer–Tropsch process. Herein, a short review of promising developments in the literature concerning the internal dry reforming of biogas (CH _4 and CO _2 ) in oxygen-ion conducting and proton-conducting fuel cells is provided. The thermodynamics of different reforming processes, the advantages, disadvantages, and the fundamental electrochemical processes in SOFCs and SPCFCs are discussed comprehensively and comparatively. In addition, this article aims to provide a perspective on current gaps and possible future research efforts.